2008
DOI: 10.1021/jp806677q
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Oriented Zinc Oxide Nanowire Array into Novel Hierarchical Structures in Aqueous Solutions

Abstract: The strategy to manipulate nanoscale building blocks into well-regulated hierarchical architectures is of great interest and valuable to both material synthesis and advanced nanodevices. Novel ZnO hierarchical structures with nanowire arrays connected on both faces of parallel ZnO hexagonal disks were produced in a facile temperature-dependent multi-step hydrothermal route within an open vessel, in which lamellar zinc hydroxide (LHS-Zn) disks were firstly formed as intermediate basic floor, whose surface may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
1
11
0
2
Order By: Relevance
“…As the growth proceeded, growth nutrient was consumed, and the precursor concentration became dilute, which induced secondary growth and a decrease in the nanowire diameter and eventually the formation of bilayered structures [207]. [208]. The ZnO nanowire arrays were connected between parallel ZnO hexagonal disks.…”
Section: Hierarchical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As the growth proceeded, growth nutrient was consumed, and the precursor concentration became dilute, which induced secondary growth and a decrease in the nanowire diameter and eventually the formation of bilayered structures [207]. [208]. The ZnO nanowire arrays were connected between parallel ZnO hexagonal disks.…”
Section: Hierarchical Structuresmentioning
confidence: 99%
“…During dehydration, many regular nanosized ZnO islands were left on the disk surface, which seeded the secondary growth of ZnO nanowires, resulting in multicell sandwiches or nanowire-disk-nanowire-disk superlattices, as shown in Fig. 20(c) [208]. Most recently, Xu et al demonstrated a novel technique for multilayer ZnO nanowire assemblies [209].…”
Section: Hierarchical Structuresmentioning
confidence: 99%
“…In recent years, semiconductor materials with different sizes and morphologies have received much attention due to their potential applications as active components or interconnect in nanoscaled electronic, optical, optoelectronic, electrochemical, and electromechanical devices [1][2][3][4][5][6]. The properties of the semiconductor nanomaterials were controlled by their chemical composition, their shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, ZnO nanostructures exhibit UV emission and visible emission. The UV emission is attributed to the near-band edge emission of ZnO due to the annihilation of excitons [24], while the visible luminescence mainly originates from the surface defect states such as Zn interstitials and oxygen vacancies [25]. One of the key issues on ZnO photoluminescence is the suppression of defect emission either by varying the preparation conditions or post-fabrication treatments [26].…”
Section: Resultsmentioning
confidence: 99%